The University of Tetova: A Glorious Temple Built on the Nation’s Sacrifice for Culture and Justice Acknowledgement (European Journal of Interdisciplinary Studies, 2019)
In different historical periods, famous people have sacrificed themselves on behalf of their substantial beliefs in the function of promoting scientific knowledge. Likewise, many of them, with an uncompromising piety have contributed to the establishment of institutions to ensure its advancement. Not long ago, by the end of the 20th century, in a Macedonian town – now North Macedonia, in Tetovo - the first Albanian-language university was founded as a product of citizens’ collective willpower for ethnic and cultural identity actualization in the field of education. It is fairly said that its founding history is hurtful and atypical for a higher education institution. Therefore, through this article we will tend to elaborate the specificities of its evolution by describing two development stories based on the collected data using the archival study method. In the first one, we will give light to some of events of essential importance of its establishment, in a time and context of communist regime that led an ethnic groups marginalization politics in a multiethnic society. Our focus will be the police actions by the government of the time in order to brutally crush the pro-University civic movement, which led to murder and imprisoning of Albanian intellectuals, professors and youngsters, but with unsuccessful epilogue. Subsequently, we will present the second story of this major national project: from the moment if its institutional legalization in 2004 to the present. Today, this university represents the nucleus of the Albanian emancipation in RNM, by promoting social, multicultural and especially scientific and academic values. At the end we will emphasize the vision, strengths of this University, such are women empowering, intercultural dialogue and its internationalization.